Pengaruh ROA dan Leverage terhadap Tax Avoidance pada Bank Umum Syariah Periode 2014-2019 - Fina Ainul Fitriya; Anton Bawono (Universitas Muhammadiyah Surabaya, 2023)
Abstract The purpose of this study is to determine and analyze the effect of ROA and leverage on tax avoidance or tax avoidance at Islamic Commercial Banks for the period 2014-219. This type of research is a quantitative study with a sample of 72 data consisting of 12 BUS that have met the purposive sampling criteria. The analytical tool used is Eviews 9 software. Data analysis methods include stationarity test, regression model test, statistical test (T test, F test, and coefficient of determination test) and classical assumption test. The results of the study indicate that profitability as proxied by ROA or Return on Assets has a significant positive effect on tax avoidance. While leverage has a significant negative effect on tax avoidance.Keywords: Tax Avoidance, ROA, Leverage, Company Size